Predictive Value Of Platelet Indices For Differentiating Hyper Destructive Thrombocytopenia From Hypo Productive Thrombocytopenia In Patients Attending Teritiary Care Hospital - Chintalapudi, Deepthi Chandrika; Yelikar, Balasaheb R; Mulimani, Mallanna S; Konduru, Anil Reddy; Nerune, Savitri M (Annals of Pathology and Laboratory Medicine, 2020)
BACKGROUND: Thrombocytopenia is one of the most critical and complicated clinical conditions to manage. Hence the need for a platelet count has increased over the years in the form of manual smear count and bone marrow examination for discriminating hyper destructive and hypo productive thrombocytopenia. The introduction of platelet indices like mean platelet volume (MPV), platelet distribution width (PDW), Platelet large cell ratio (PLCR) in automated haematology analyzers has provided a window into the cause of thrombocytopenia in the recent years. Hence this study was undertaken to analyze the utility of these platelet indices in hypo productive and hyper destructive thrombocytopenia. METHODS: A prospective cross-sectional study was conducted on 84 thrombocytopenic patients out of which 49 were hyper destructive and 35 were hypo productive group. The blood samples were analyzed for CBC diff using SYSMEX XN 1000. Statistical analysis was performed to assess the mean SD, Receiver Operating Curve (ROC) to determine the specificity, sensitivity, positive predictive value (PPV) and negative predictive values (NPV) for platelet parameters. Correlation test to determine association between the continuous variables was done. RESULT: All platelet indices were significantly higher in hyper destructive than in hypo productive group. The MPV and PLCR showed better sensitivity and specificity, positive and negative predictive values when compared to PDW in both the groups. There was statistically significant correlation and difference of platelet parameters like MPV, PDW and PLCR between the hyper destructive and hypo productive thrombocytopenia. CONCLUSION: The platelet indices MPV and PLCR have better ability to discriminate hyper destructive from hypo productive thrombocytopenia. Evaluating these parameters offers an earlier diagnosis in hyper destructive thrombocytopenia patients avoiding, bone marrow aspiration and even prevent undesirable platelet transfusion.